2021
DOI: 10.53703/001c.29484
|View full text |Cite
|
Sign up to set email alerts
|

Flexing the Leadership Muscle: An International Study of Entrepreneurial Resilience in Rural Communities During the COVID-19 Pandemic

Abstract: The COVID-19 global crisis and the ensuing lockdown of large parts of society and economic life has been an exogenous shock to society (Kuckertz et al., 2020). It is predicted the impact on the small business sector is likely to be severe (Fairlie, 2020). The findings of this international qualitative study offer a first-hand and real-time account of the adversity encountered by small rural businesses during the first lockdown in the COVID-19 pandemic and insight into how their leaders exercised resilience. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Also, resilience capacities can mitigate the psychosocial impact of crises and disasters by providing a sense of routine, stability, structure, and hope for the future. Research showed that "personal and business experience of crises, positive mindset, personal faith, learning and leading, and relationships" enhance entrepreneurial resiliency (Hutchinson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Also, resilience capacities can mitigate the psychosocial impact of crises and disasters by providing a sense of routine, stability, structure, and hope for the future. Research showed that "personal and business experience of crises, positive mindset, personal faith, learning and leading, and relationships" enhance entrepreneurial resiliency (Hutchinson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by the study of Hutchinson et al (2021) that personal and business experiences of crisis help business owners to exercise entrepreneurial resilience effectively. The experience earns by the firms as they grow older and in the due process the firm learns how to handle rapidly changing internal and external environments successfully.…”
Section: Hypothesis 2 the Firms' Size Increases Firms Resiliency And ...mentioning
confidence: 99%
“…Resilience is defined as the ability of any firm to absorb, respond, and retrieve from situations that could threaten its existence while the sustained growth rate is a rate that can be achieved by the firm on its internal resources without any external support. Most of the available studies examined the issue of resilience and sustaining the growth of small firms from the perspective of entrepreneurial intention (Jena, 2022), strategic agility and its association with firm age, firm size, and firm performance (Reed, 2021), leadership practices and entrepreneurial resiliency (Hutchinson et al, 2021), strategic entrepreneurship for disrupted firms (Thomas & Douglas, 2021), and entrepreneurs' personality traits of resilience and high-power distance impact on consumers' evaluations of sustainability practices (Vizcaíno et al, 2021). These factors are perfectly applicable in normal predictable conditions to analyze the sustainability and resilience of firms.…”
Section: Introductionmentioning
confidence: 99%
“…This impact is not only limited to large companies but Recent studies have also focused on the theme of organizational resilience, particularly in the context of the global pandemic. Hutchinson et al (2021) investigated how small business entrepreneurs exhibited resilience in navigating the crisis, while Prayag et al (2019) explored the impact of individual resilience on the resilience of a tourism community in New Zealand and its effect on life satisfaction. Besides, Ngoc Su et al (2021) examined the strategies employed by the hospitality sector in Vietnam in response to the sudden lockdown caused by the pandemic, including defensive strategies such as enforcing health and safety protocols and offensive strategies such as talent management and resource network enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ever since the pandemic became a global economic crisis over two years, this innate organizational ability to overcome crises and become successful has been a recent research theme surrounding resilience. For instance, Hutchinson et al (2021) studied how small business entrepreneurs "flex their leadership muscle" in navigating the crisis and come through successfully by exercising resilience. Moreover, Prayag et al (2019) extensively studied a tourism community wrecked by a recent earthquake in New Zealand.…”
Section: Introductionmentioning
confidence: 99%